Neuroscience and oncology: state-of-the-art and new perspectives - Winkler, Frank (Current opinion in neurology, 2023)
Purpose of review - Emerging discoveries suggest that both the central (CNS) and peripheral (PNS) nervous system are an important driver of cancer initiation, promotion, dissemination, and therapy resistance, not only in the brain but also in multiple cancer types throughout the body. This article highlights the most recent developments in this emerging field of research over the last year and provides a roadmap for the future, emphasizing its translational potential. - Recent findings - Excitatory synapses between neurons and cancer cells that drive growth and invasion have been detected and characterized. In addition, a plethora of paracrine, mostly tumor-promoting neuro-cancer interactions are reported, and a neuro-immuno-cancer axis emerges. Cancer cell-intrinsic neural properties, and cancer (therapy) effects on the nervous system that cause morbidity in patients and can establish harmful feedback loops receive increasing attention. Despite the relative novelty of these findings, ther - apies that inhibit key mechanisms of this neuro-cancer crosstalk are developed, and already tested in clinical trials, largely by repurposing of approved drugs. - Summary - Neuro-cancer interactions are manyfold, have multiple clinical implications, and can lead to novel neuroscience-instructed cancer therapies and improved therapies of neurological dysfunctions and cancer pain. The development of biomarkers and identification of most promising therapeutic targets is crucial.
Gesehen am 04.06.2024